DINAMIKA KETERLIBATAN BERBAGAI KELOMPOK KEPENTINGAN DI PULAU REMPANG SEBAGAI PROYEK STRATEGIS NASIONAL (PSN) - Rinaldi, Alyssa Zalfanda; Alfalin, Indra; Phillianova, Laqisya; Saputra, Satria Andrean (Jurnal Administrative Reform, 2025)
This study analyzes the dynamics of various interest groups' involvement in the conflict surrounding the development of Rempang Eco-City as a National Strategic Project in Rempang Island, Batam. Using a comparative study approach and political economy perspective, the research examines the roles of the government, local communities, and investors in influencing the conflict related to land acquisition and social rights. The main focus is the tension between pro-growth and anti-growth coalitions, as well as the role of mass media in shaping public perceptions. The study aims to provide insights into agrarian conflict dynamics and infrastructure development, with policy recommendations for resolving similar conflicts in the future.